REMOTE PSYCHIATRIC AND PSYCHOLOGICAL SERVICES VIA THE COMMUNICATIONS TECHNOLOGY SATELLITE (CTS) / SERVICES PSYCHIATRIQUES ET PSYCHOLOGIQUES A DISTANCE PAR LES COMMUNICATIONS SATELLITE (CTS) - Covey, H. Dominic; Heseltine, Gilbert F.D.; Evans, David; Gliksman, Louis (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see pdf